Bayesian correction for mortality trend of oral cavity cancer - Pourhoseingholi, Mohamad Amin (Research Institute for Gastroenterology and Liver Diseases, 2012)
AIM: The aim of this study is to estimate oral cavity cancer mortality for Iranian population, using Bayesian approach in order to revise this misclassification. BACKGROUND: Mortality is a familiar projection to address the burden of cancers, but according to Iranian death registry, about 20% death statistics were still recorded in misclassified categories. PATIENTS AND METHODS: We analyzed national death statistic reported by the Iranian Ministry of Health and Medical Education from 1995 to 2004 stratified by age group, sex, and cause of death are included in this analysis. Oral cavity cancer [ICD-10; C00-08] were expressed as the annual mortality rates/100,000, overall, by sex and by age group (<50 and ≥50 years of age) and age standardized rate (ASR). The Bayesian approach to correct and account for misclassification effects in Poisson count regression with a beta prior employed to estimate the mortality rate of EC in age and sex group. RESULTS: According to the Bayesian re-estimate there were between 20 to 30 percent underreported mortality records in death due to oral cavity cancer. The age standardized mortality rate of oral cavity cancer increased dramatically during these years, Age specific rate for oral cavity cancer indicated higher mortality rate for older age. CONCLUSION: Our findings suggested a substantial undercount of oral cavity cancer mortality in Iranian population. So policy makers who determine research and treatment priorities on death rates should notice to this underreported data.